Manual of electrophysiology - Chatterjee, Kanu (New Delhi : Jaypee Brothers Medical Publishers, 2015)
Manual of Electrophysiology is a comprehensive guide to cardiac electrophysiology, brought together by a team of US based experts in this field. The book focuses on current understanding and the most recent advances in electrophysiology. Consisting of 16 chapters, the book begins with basic understanding of the mechanisms of arrhythmia (irregular heartbeat), the pharmacology of antiarrhythmic drugs, and an introduction to electrophysiology studies. Various arrhythmias are discussed in detail, from tachycardia and bradycardia to cardiomyopathy and Brugada Syndrome. The latter part of the book provides a number of therapeutic guidelines for heart conditions, including surgical and catheter ablation of cardiac arrhythmias, cardiac resynchronisation therapy and ambulatory electrocardiographic monitoring.
Arrhythmia mechanisms -- Antiarrhythmic drugs -- Electrophysiology studies -- Syncope -- Atrial fibrillation -- Supraventricular tachycardia -- Clinical spectrum of ventricular tachycardia -- Bradycardia and heart block -- Arrhythmogenic right ventricular dysplasia/cardiomyopathy -- Long QT, short QT and Brugada syndromes -- Surgical and catheter ablation of cardiac arrhythmias -- Cardiac resynchronization therapy -- Ambulatory electrocardiographic monitoring -- Cardiac arrest and resuscistation -- Risk stratification for sudden cardiac death -- Cardiocerebral resusciation for primary cardiac arrest.
Includes bibliographical references and index.
Keywords: Electrophysiologic Techniques, Cardiac -- Handbooks; Arrhythmia; Electrophysiology; Heart -- Electric properties; Handbooks and manuals